Analisis Peran Pusat PertanggungjawabanDalam Pengelolaan Biaya Dan Pendapatan Di Sektor Publik - Andhika Eriz Putra A; Nufus; Talitha Aurellia A; Nadhirah Hamida; Elza Ariantono; Naufal Galih Yulianto (Jejak digital: Jurnal Ilmiah Multidisiplin, 2025)
This study examines the role of accountability centers as effective management tools in managing costs and revenues in the public sector. Accountability centers serve to control operational costs while optimizing revenues by increasing the transparency and accountability of government agencies. This study uses a qualitative approach through case study analysis of various government agencies in Indonesia, involving interviews, observations, and analysis of official documents. The results show that the implementation of accountability centers can help improve budget efficiency and support decision-making based on accurate financial data. However, the successful implementation of accountability centers depends heavily on the readiness of human resources, the support of an integrated financial management information system, and the commitment of agency leaders. Obstacles such as limited human resource capacity and suboptimal information systems remain major challenges. This study concludes that accountability centers are an important instrument in public sector financial control that can lead to more effective cost and revenue management if balanced with management reform and continuous training. The implications of this study provide practical recommendations for government agencies to strengthen the functionality of accountability centers in order to achieve better financial management and optimal public services.